Optical fiber-based open source low cost portable spectrometer system - Tunens, Gatis; Einbergs, Ernests; Laganovska, Katrina; Zolotarjovs, Aleksejs; Vilks, Karlis; Skuja, Linards; Smits, Krisjanis (Elsevier Ltd, 2024)
This article explores the development of a small, compact fiber-based spectrometer system designed to overcome the limitations of standard spectrometers, such as the high cost and restricted accessibility. Operated by a Raspberry Pi, the fiber-based spectrometer system uses the increased computing power to provide versatile modes of operation and powerful data processing, while maintaining a small size. Specifically crafted for basic chemistry and biology lab setups, where fibers allow measurements in different conditions, and customization enables fluorescence, light scattering, and absorption measurements. The system is adaptable and versatile, offering ease of modification and adaptation for a broad range of applications. © 2024 The Author(s) --//-- This is an open-access article Tunens, Gatis, Einbergs, Ernests, Laganovska, Katrina, Zolotarjovs, Aleksejs, Vilks, Karlis, Skuja, Linards, Smits, Krisjanis, Optical fiber-based open source low cost portable spectrometer system, HardwareX, 2024, Volume 18, Article number e00530, doi: 10.1016/j.ohx.2024.e00530.
This work was funded by the European Regional Development Fund project [Nr. 1.1.1.1/21/A/053]. University of Latvia as the Center of Excellence acknowledges the financial support from the European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2. This study is based upon work from COST Action CA16215 (PortASAP - European network for the promotion of portable, affordable and simple analytical platforms).
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Absorption; Fibers; Fluorescence; Spectroscopy